Sustainable material choice for construction projects: A Life Cycle Sustainability Assessment framework based on BIM and Fuzzy-AHP - Figueiredo, Karoline; Pierott, Rodrigo; Hammad, Ahmed W.A.; Haddad, Assed (Building and environment, 2021)
Construction professionals and researchers are increasingly looking for sustainable solutions for buildings in a bid to reduce some of the negative impacts associated with the sector. A common misconception is to consider sustainability as only concerning environmental issues, without regard for the interaction between a triple bottom line framework that is comprised of social, economic, and environmental factors. Material choice is known to impact building sustainability directly since the use of certain materials can dramatically alter the footprint generated over the life cycle of the building. However, the construction industry is not yet equipped with approaches that simultaneously account for all three aspects of sustainability when it comes to deciding on materials to adopt. This paper proposes a decision-making framework for construction professionals and researchers involving the integration of Life Cycle Sustainability Assessment (LCSA), Multi-Criteria Decision Analysis (MCDA), and Building Information Modeling (BIM) to choose suitable materials for buildings. The framework is built based on a literature review of relevant papers to identify critical factors and challenges to implementing this integration. The Fuzzy Analytic Hierarchy Process was chosen as the MCDA method within the proposed framework, given that the problem of material choice often contains subjectivity, uncertainty, and ambiguity, which is best solved with fuzzy logic. A residential building was adopted as a case study to validate the proposed framework, and the LCSA method is applied, covering the construction, operation, and end-of-life phases of the building. [Display omitted] •An innovative integration is proposed to improve building material selection.•Different materials can be tested with the proposed LCSA-BIM-MCDA integration.•Decision-making is facilitated, covering environmental, economic and social impacts.•BIM is used to improve LCI data collection and facilitate the impact calculation.•Fuzzy-AHP based on constrained fuzzy arithmetic is used as the MCDA method.